Enhanced electronic communication through a conjugated bridge in a porphyrin–fullerene donor–acceptor couple. Issue 33 (5th July 2021) - Caballero, Rubén; Calbo, Joaquín; Aragó, Juan; de la Cruz, Pilar; Ortí, Enrique; Tkachenko, Nikolai V.; Langa, Fernando
Abstract : The electronic communication between the terminal electron-donor ZnP and electron-acceptor C60 units is enhanced by the conjugated EDOTV-based spacer leading to photoinduced electron transfer over the distance >2 nm in the picosecond time domain. Abstract : A ZnP–2EDOTV–C60 triad, with enhanced electronic communication between terminus donor and acceptor moieties, was synthesized and studied both experimentally and theoretically. Electrochemical measurements and density functional theory calculations support that the first oxidation takes place on the 3, 4-ethylenedioxythiophenevinylene (2EDOTV) bridge followed by the oxidation of the ZnP moiety at slightly higher energies. The electronic communication between the terminal electron-donor ZnP and the electron-acceptor C60 units is enhanced by the conjugated EDOTV-based spacer leading to photoinduced electron transfer over the distance >2 nm in the picosecond time domain. The involvement of the spacer in the electron transfer is confirmed by both photophysical measurements and theoretical calculations indicating the formation of intermediate ZnP–2EDOTV δ + –C60 δ − charge-transfer states. Overall, the enhanced donor–acceptor electronic communication accelerates the photoinduced charge separation but also affects the charge recombination process.